Glial swelling and astrogliosis produce diffusion barriers in the rat spinal cord - Syková, E; Vargová, L; Prokopová, S; Simonová, Z (Glia, 1999)
Cell swelling and astrogliosis (manifested as an increase in GFAP) were evoked in isolated rat spinal cords of 4-21-day-old rats by incubation in either 50 mM K+ or hypotonic solution (235 mosmol kg(-1)). Application of K+ and hypotonic solution resulted at first in a decrease of extracellular space (ECS) volume fraction alpha (ECS volume/total tissue volume) and an increase in tortuosity lambda (lambda2 = free/apparent diffusion coefficient) in spinal gray (GM) and white matter (WM). These changes resulted from cell swelling, since the total water content (TW) in spinal cord was unchanged and the changes were blocked in Cl- -free solution and slowed down by furosemide and bumetanide. Diffusion in WM was anisotropic, i.e., more facilitated along fibers (x-axis) than across them (y- or z-axis). The increase of lambda(y,z) was greater than that of lambda(x), reaching unusually high values above 2.4. In GM only, during continuous 45 min application, alpha and lambda started to return towards control values, apparently due to cell shrinkage of previously swollen cells since TW remained unchanged. This return was blocked by fluoroacetate, suggesting that most of the changes were due to the swelling of glia. A 45 min application of 50 mM K+ and, to a lesser degree, of hypotonic solution evoked astrogliosis, which persisted after washing out these solutions with physiological saline. During astrogliosis lambda increased again to values as high as 2.0, while alpha either returned to or increased above control values. This persistent increase in lambda after washout was also found in WM, and, in addition, the typical diffusion anisotropy was diminished. Our data show that glial swelling and astrogliosis are associated with a persistent increase in ECS diffusion barriers. This could lead to the impairment of the diffusion of neuroactive substances, extrasynaptic transmission, "crosstalk" between synapses and neuron-glia communication.
Keywords: Oligodendroglia; draslík; mícha; astrocyty; Neuronal Plasticity; nervový přenos; Neuroglia; difuze; krysa rodu Rattus; Synaptic Transmission; tělesná voda; neuroplasticita; Body Water; imunohistochemie; oligodendroglie; potkani Wistar; Immunohistochemistry; Rats, Wistar; velikost buňky; Astrocytes; hypotonické roztoky; Potassium; Spinal Cord; zvířata; neuroglie; Cell Size; Rats; Animals; Diffusion; Hypotonic Solutions